2015
DOI: 10.1136/bmjqs-2015-004171
|View full text |Cite
|
Sign up to set email alerts
|

Observation for assessment of clinician performance: a narrative review

Abstract: Observations are useful for the improvement of healthcare delivery through the identification of clinician lapses and weaknesses that affect quality and safety. Limitations of observations include the Hawthorne effect and the necessity of trained observers to capture and analyse the notes or videos. The comprehensive, subtle and sensitive information observations provided can supplement traditional quality assessment methods and inform targeted interventions to improve patient safety and the quality of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 80 publications
0
47
0
Order By: Relevance
“…Indeed the ACGME milestones, which call for the evaluation of specific clinical knowledge, attitudes and skills, essentially require the observation of trainees in many domains. The practice of clinical observation typically ends once doctors transition out of training despite being an aspect of continuing quality assessment in other high‐impact fields, such as aviation and teaching . Although there are indirect ways that doctors demonstrate competence, most practicing doctors have not been observed and critiqued in the actual practice of medicine since they completed training.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed the ACGME milestones, which call for the evaluation of specific clinical knowledge, attitudes and skills, essentially require the observation of trainees in many domains. The practice of clinical observation typically ends once doctors transition out of training despite being an aspect of continuing quality assessment in other high‐impact fields, such as aviation and teaching . Although there are indirect ways that doctors demonstrate competence, most practicing doctors have not been observed and critiqued in the actual practice of medicine since they completed training.…”
Section: Introductionmentioning
confidence: 99%
“…But shadowing involves a more intimate experience—what Czarniawska defines a ‘peculiar twosome’ 11. Most ethical guidelines suggest that observers should not participate in the clinical process, but in extreme circumstances they may be ethically bound to intervene 1. The possibility of intervening becomes acute when shadowers know more about what is going on than do patients and families.…”
Section: Challengesmentioning
confidence: 99%
“…A recently published study by Yanes et al 1 suggests that observation in clinical environments may have an especially valuable role in capturing the organisational and situational factors that shape clinical processes. In data-dense and high-risk environments, observation sheds light on the specific subprocesses of complex clinical activities (eg, information transfer, communication patterns, distractions) and their effects on patient care.…”
Section: Introductionmentioning
confidence: 99%
“…When trainees' surgical skill and non-technical skill is assessed through video reordering, as opposed to live and inperson evaluation, there is a lessening of the Hawthorne Effect, a phenomenon wherein trainees change their behavior in the presence of an examiner or rater. In a systematic review of observation-based assessment, Yanes et al [9] found that the Hawthorne Effect may artificially raise performance standards in observational studies. Yanes points out that if video recording is done correctly, the risk of the Hawthorne Effect is low, especially in high-risk or crisis scenarios where attention is directed elsewhere.…”
Section: Why Do We Need Video Analysis In Surgery?mentioning
confidence: 99%